The Roles of Myeloid-Derived Suppressor Cells in Liver Disease - Chunye Zhang; Yuxiang Sui; Shuai Liu; Ming Yang (Biomedicines, 2024)
Liver disease-related mortality is a major cause of death worldwide. Hepatic innate and adaptive immune cells play diverse roles in liver homeostasis and disease. Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells. MDSCs can be broadly divided into monocytic MDSCs and polymorphonuclear or granulocytic MDSCs, and they functionally interact with both liver parenchymal and nonparenchymal cells, such as hepatocytes and regulatory T cells, to impact liver disease progression. The infiltration and activation of MDSCs in liver disease can be regulated by inflammatory chemokines and cytokines, tumor-associated fibroblasts, epigenetic regulation factors, and gut microbiota during liver injury and cancer. Given the pivotal roles of MDSCs in advanced liver diseases, they can be targeted to treat primary and metastatic liver cancer, liver generation, alcoholic and nonalcoholic liver disease, and autoimmune hepatitis. Currently, several treatments such as the antioxidant and anti-inflammatory agent berberine are under preclinical and clinical investigation to evaluate their therapeutic efficacy on liver disease and their effect on MDSC infiltration and function. Phenotypic alteration of MDSCs in different liver diseases that are in a model-dependent manner and lack special markers for distinct MDSCs are challenges for targeting MDSCs to treat liver disease. Multi-omics study is an option to uncover the features of disease-specific MDSCs and potential gene or protein targets for liver disease treatment. In summary, MDSCs play important roles in the pathogenesis and progression of liver disease by regulating both intrahepatic innate and adaptive immune responses.